Merespons Persoalan Kontemporer dengan Dakwah Inklusif sebagai Komunikasi Humanis - Anja Kusuma Atmaja (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2020)
A Muslim's struggle is to conquer his own desires. Encourage all people to do good to carry out the commands given by Allah SWT through religious orders delivered through the Prophet Muhammad who are recorded in the Qur'an and Hadith. Every Muslim has the obligation to convey what is true in accordance with religious guidance. In connection with the da'wah of Islam, a messenger of the message of da'wah is the successor of the Prophets and Apostles for inviting the truth. However, today we often see and listen to lectures that are conceptualized in a good way but the contents conveyed tend to be tendentious and unsettling the Ummah. Da'wah that is delivered is often only focused on problems that can actually be overcome by the spirit of humanity. However, this method is feared will instead give the impression that preaching must be loud and loud. Whereas the inclusive way of preaching has been taught by Rasulullah Saw which emphasizes human relations.